ADMIRAL ZHENGHE AND THE WEST: : A COMPARATIVE ANALYSIS IN CONFUCIAN AND CHRISTIAN CIVILIZATION POWERS - Chang, Peter T. C. (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2021)
Zhenghe’s epoch-making voyages and the subsequent European expansive maritime exploration have exacted varied historical impacts and impressions upon the world. This paper argues that the contrasts stem from their radically different underlying belief systems, namely Confucianism and Christianity. In the East, the Confucian’s monistic and polytheistic ethos, coupled with a sanguine and circular worldview, underpinned Imperial China’s multilateral and restrained approach in dealing with the outside world. In the West, the Christian’s dualistic and monotheistic creed, together with a melancholic and linear worldview, moulded European Imperialism’s unilateral and forthright strategy to transform the world. Aside from the past, these divergent philosophical and religious worldviews continue to affect the present, including the current China and US geopolitical and civilizational rivalry.